FAKTOR PENDUKUNG DAN PENGHAMBAT PELATIHAN BARISTA DI BLK KABUPATEN KARAWANG - Mayumi Rezkya; Ika Rizqi Meilya; Ratna Sari Dewi (Jurnal Pendidikan Sepanjang Hayat, 2026)
This study investigates the supporting and inhibiting factors of the barista training program in enhancing entrepreneurial competence at the Balai Latihan Kerja (BLK) in Karawang Regency. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation. Informants included one staff member, one instructor, and four training participants. The results show that internal supporting factors include relevant training materials, skilled instructors, and participant motivation driven by personal and economic needs. External supports include adequate facilities, high public interest in the barista profession, and strong family support. However, several challenges were identified. Internal obstacles involve reduced training time due to budget efficiency, varying participant attitudes, and feelings of insecurity. External challenges include equipment limitations, vendor errors in material delivery, and lack of participant commitment. Overall, the success of the barista training program is influenced by both internal motivation and external conditions that must be managed effectively.